THE EFFECT OF SURFACE ROUGHNESS ON THE SOIL LOSS - Khalid F. Hassan (Mesopotamia Journal of Agriculture)
Field measurements and lab analysis were conducted to determine the effect of soil surface roughness ( oriented and random) resulted from discing and chiseling on the soil loss by wind erosion. Some soil ridges parameters were measured in the field and aggregation (clods and non-erodible aggregates) were determined in the lab. The soil loss of the two operations was determined as a function of these variables. The results showed that the large proportions of random roughness(large clods) and clear oriented roughness (soil ridges) in the tilled layer after soil discing have a greatest effect in reducing the amount of soil loss and potential erosivity of soil by wind action in comparison with soil chiseling .This is attributed to the fact that the soil clods easily crushed into fine aggregates after soil chiseling but remained unchanged in soil discing .The statistical analysis coming in agreement with the results of the lab and field investigation